Accelerated vs. conventionally fractionated postoperative radiotherapy of non-small cell lung cancer: final results of the prematurely terminated PORTAF trial - Bütof, Rebecca; Koi, Lydia; Löck, Steffen; Appold, Steffen; Drewes, Steffen; Koschel, Dirk; Kotzerke, Jörg; Nestle, Ursula; Adebahr, Sonja; Zips, Daniel; Heinzelmann, Frank; Hehr, Thomas; et al. (Strahlentherapie und Onkologie, 2025)
A prolonged overall treatment time (OTT) has been demonstrated to adversely affect the primary radiation therapy (RT) outcome in various solid tumors, including non-small cell lung cancer (NSCLC). Retrospective data from our group suggested an advantage of shorter OTT also for postoperative RT (PORT) in patients with NSCLC. The PORTAF trial (ClinicalTrials.gov: NCT02189967) was initiated to prospectively test this hypothesis.